Tourists’ Expectation and Perception Regarding Holiday in Jakarta, Indonesia - HENDIJANI, Roozbeh Babolian; SULISTYO, L. Iswi Hapsari (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).22, 2017)
International tourists’ arrival in Jakarta is growing in the past few years. It is important to know tourists’ expectation before visiting Jakarta and their experience afterwards. Hence, marketers can maintain the long term viability of Jakarta as a tourist destination. The aim of this research is to evaluate the successful promoting of Jakarta’s image as a tourist destination through comparing the differences between expectation and experiences of tourists. It also examines the relationship between destination experiences towards revisit intention. Quantitative approach was employed to conduct the analysis through self-administrated questionnaire. Statistical analysis such as descriptive analysis, multiple linear regression and paired sample t-test were conducted. The results depicted the differences between expectation and experiences of tourists in Jakarta. Based on the findings, it is suggested aggressive and continuous efforts should be taken in Jakarta to create alluring destination experience.